Perturbing the spin crossover transition activation energies in Fe(H2B(pz)2)2(bipy) with zwitterionic additions. (5th July 2018) - Costa, Paulo; Hao, Guanhua; N'Diaye, Alpha T; Routaboul, Lucie; Braunstein, Pierre; Zhang, Xin; Zhang, Jian; Doudin, Bernard; Enders, Axel; Dowben, Peter A
Abstract: A thermal component to the soft x-ray induced spin crossover transition exists in the switching of a spin crossover compound (complex [Fe{H2 B(pz)2 }2 (bipy)] (pz  =  pyrazol-1-yl, bipy  =  2, 2′-bipyridine) combined with the dipolar molecular additives (zwitterionic p -benzoquinonemonoimine C6 H2 ( )2 ( )2 ). The addition of the zwitterionic molecule locks the Fe(II) complex in a largely low spin state configuration over an unusually broad temperature range that includes temperatures well above the thermal spin crossover temperature of 160 K. It is demonstrated here that the process of exciting the [Fe{H2 B(pz)2 }2 (bipy)] moiety, in the presence of with C6 H2 ( )2 ( )2, to an electronic state characteristic of the high spin state though incident x-ray fluences, has a thermal activation energies are determined to 14–18 meV for a range of mixing ratios from 1:2 to 1:10. Those activation energies are also significantly reduced as compared to values of 60–80 meV found for nanometer thin films of [Fe{H2 B(pz)2 }2 (bipy)] on SiO2 .